PROFILE OF STUDENTS’ METACOGNITIVE THINKING SKILLS VIEWED FROM PARENTING STYLE OF THE PARENTS - Tuti Alawiyah Rahman; Devy Sekar Ayu Ningrum (Universitas Pendidikan Indonesia, 2022)
Abstract: The purpose of this study is to describe the profile of students’ metacognitive thinking skills viewed from parenting style of the parents. The present study involves 210 undergraduate students of Siliwangi Institute of Education from seven study programs who were selected randomly. Metacognitive Thinking Skills Scale which is adapted from Tuncer and Kaysi (2013) were administered to the sample to rate students’ metacognitive thinking skills which covers three dimensions namely reflective thinking ability for problem solving, decision making ability, and alternative Strategy ability. The second instrument used in this study was the instrument of Parenting Style Questionnaire (PSQ) adapted from Robinson, C., Mandleco, B., Olsen, S. F., Hart, C. H. (1995) to assess the students’ background of parenting style of their parents. The research finding showed that there were differences in metacognitive thinking skills between students with authoritative, authoritarian, and permissive parenting backgrounds, both on metacognitive thinking skills as a whole and in its aspects. The research result can be used as need assessment for the development of metacognition-based academic counseling and guidance programs.